Nutritional Intake Differences of Children Aged 6-23 Months in Coastal and Non-Coastal Stunting Areas - Muhammad Irwan Setiawan; Fahrini Yulidasari; Atikah Rahayu; Ayunina Rizky Ferdina (Jurnal Berkala Kesehatan, 2023)
Stunting is still a health concern in developing countries. The purpose of this study was to analyze the differences in nutritional intake of children in the Coastal (Co) and Non-Coastal (NCo) Stunting Areas in Tanah-Laut. The quantitative cross-sectional study design was carried out on subjects aged 6-23 months with a total of 65 Co and 66 NCo toddlers who were physically healthy and were still breastfeeding. The instruments included a questionnaire, a 24-hour recall form, a stature meter, and a digital scale. The univariate analyses to describe the frequency and median data. The Mann-Whitney test was used to see differences in intake of macro and micro nutrients in both regions. The prevalence of stunting in NCo 21.2%, while in Co 18.4%. About 7.6% NCo and 26.2% Co were malnourished. The prevalence of wasting was 13.6% and 15.4%. There was a significant difference in Energy, Carbohydrates, fat (p<0.05). There was no difference in protein intake between two regions. Both micronutrients were classified as deficient. There were differences of vitamin-A, vitamin-D, vitamin-K, calcium, and iron intake. Either macronutrient intake was sufficient, but neither for micronutrients. There was no significant difference in protein intake between the two groups